Epidemiological survey of swine cysticercosis using ante-mortem and post-mortem examination tests in the southern highlands of Tanzania - Boa, M.E.; Mahundi, E.A.; Kassuku, A.A.; Willingham, Arve Lee; Kyvsgaard, N.C. (Elsevier, 2006)
Pig keeping is known to be popular in the regions of the southern highlands zone (Mbeya, Iringa and Ruvuma) of Tanzania where more than 60% of pigs under the small-scale production system are raised. However, no epidemiological surveys on porcine cysticercosis have been conducted in the zone in spite of unofficial reports indicating the disease to be a widespread problem. To estimate prevalence rates and risk factors for porcine cysticercosis in Chunya and Iringa Rural Districts and Ruvuma Region (Songea and Mbinga Districts), 722, 808 and 302 live pigs, respectively, were examined by lingually and the prevalence of swine cysticercosis was found to be 7.6%, 8.4% and 16.9% for Chunya and Iringa Rural Districts, and Ruvuma Region, respectively. Structured observations and questionnaire interviews were used to analyse pig rearing practices and household use of latrines in Chunya and Iringa Rural Districts only. The analysis of effect of pig management practices, lack of a latrine, eating undercooked pork, home slaughter and no inspection of pork and lack of knowledge of T. solium on their association to tongue positivity in pigs was done by means of a contingency table. Odds ratios (OR) with corresponding 95% confidence intervals (95% CI) and p-values were calculated. Structured questionnaire interviews identified factors associated with the disease prevalence in both Chunya and Iringa Rural Districts were free-ranging of pigs, home slaughtering of pigs and pork not being inspected. While in Chunya and Iringa Rural Districts lack of latrine and barbecuing were found a risk factor, respectively. To control the disease in the study areas of the southern highlands there is a need for significant improvements regarding the use of latrines, confinement of pigs, pork inspection and thorough cooking of pork.